I just don't know what to do with the negative exponents.

Remember the following rules when dealing with exponents.

a^{m}*a^{n} = a^{m+n}.

a^{m}/a^{n} = a^{m-n}.

a^{-n} = 1/a^{n}.

Also remember that

a^{0} = 1.

Also it may help to remember that you can regroup the terms according to bases.

To illustrate I'll use another example, and leave yours for you to try.

2*x(9*x*y^{3})(3*x^{-2}y^{4}) = (2*9*3)(x*x*x^{-2})(y^{3}*y^{4}).

I hope that helps some.

Try a bit of this, and if you still need help, I or another tutor here will be happy to assist you.